2017
DOI: 10.30574/gscbps.2017.1.1.0006
|View full text |Cite
|
Sign up to set email alerts
|

Activities of neem and wood ash as biopesticides in the control of insect pests on vegetable crops in Mubi

Abstract: The study was carried out to evaluate the efficacy of neem and wood ash for the control of insect pests infesting three vegetables in the gardening; okra, spinach and sorrel. The plants were sown in a randomize complete block design (RCBD) with four replications. Treatment application starts immediately after germination and continued on 3 days interval. Parameters observed were number of damages and number of insect infestation. These were noted after 6 and 9 weeks of germination. Data collected was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The results is with conformity with Wahedi, et al [33]; Ogbedeh and Ani [34] who reported that wood ash protects garden plants more than neem leaf powder, although all confirmed their efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results is with conformity with Wahedi, et al [33]; Ogbedeh and Ani [34] who reported that wood ash protects garden plants more than neem leaf powder, although all confirmed their efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Ogbuehi [32] reported that palm bunch ash can be used to amend pH of highly acidic soils as well as a nutrient supplement in soils with leached nutrients. Wahedi, et al [33]; Ogbedeh and Ani [34] in their studies concluded that palm bunch ash and neem leaf powder each consistently suppressed insects' incidence and severity. But the suppressive ability of palm bunch ash to insect incidence and severity increased with increase in rate of application [34,35], and the insecticidal properties of ashes vary according to the plant species [36].…”
Section: Introductionmentioning
confidence: 99%
“…The substance(s) may be able to kill or deter pests and/or pathogens of Chinese cabbage. The result of this study is in conformity with Demissie et al (2008) and Wahedi et al (2017) who demonstrated the effectiveness of wood ash against pest infestation in okra, spinach, sorrel and maize in Ethiopia and Nigeria. Additionally wood ash was found to have repulsive property against vegetable pests (Mooya, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This could be due to the short duration of pesticidal efficacy and its potassium content affecting plant height. [26] reported that wood ash applied at 3-day intervals significantly reduced pest infestation and its protectant effect was due to the presence of potash which contains potassium. Ash concentration above 70% was found to have a deleterious effect on tomato growth [27].…”
Section: Effects Of Plant-derived Pesticides On Faw Infestation and T...mentioning
confidence: 99%